2022
DOI: 10.3390/nu14132654
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Derived Metabolites and Cardiovascular Disease Risk: A Systematic Review of Prospective Cohort Studies

Abstract: Gut microbiota-derived metabolites have recently attracted considerable attention due to their role in host-microbial crosstalk and their link with cardiovascular health. The MEDLINE-PubMed and Elsevier’s Scopus databases were searched up to June 2022 for studies evaluating the association of baseline circulating levels of trimethylamine N-oxide (TMAO), secondary bile acids, short-chain fatty acids (SCFAs), branched-chain amino acids (BCAAs), tryptophan and indole derivatives, with risk of cardiovascular disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Gut microbiota-derived metabolites, such as short-chain fatty acids, BAs, catechin, and TMAO, are the direct factors causing CVDs, and have been viewed as a new breakthrough for the prevention and treatment of CVDs ( 27 , 28 ). TMAO keeps increasing the risks of CVDs after excluding other risk factors for CVDs, demonstrating a strong association between high circulating levels of TMAO and the risk and mortality of CVDs ( 29 , 30 ). Consequently, a high circulating level of TMAO is a potential marker to better stratify CVDs risks and predict short- and long-term major adverse cardiac events ( 31 ).…”
Section: Tmao and Cvdsmentioning
confidence: 99%
“…Gut microbiota-derived metabolites, such as short-chain fatty acids, BAs, catechin, and TMAO, are the direct factors causing CVDs, and have been viewed as a new breakthrough for the prevention and treatment of CVDs ( 27 , 28 ). TMAO keeps increasing the risks of CVDs after excluding other risk factors for CVDs, demonstrating a strong association between high circulating levels of TMAO and the risk and mortality of CVDs ( 29 , 30 ). Consequently, a high circulating level of TMAO is a potential marker to better stratify CVDs risks and predict short- and long-term major adverse cardiac events ( 31 ).…”
Section: Tmao and Cvdsmentioning
confidence: 99%
“…Indeed, it is now widely accepted that the microbial diversity of the gut is strictly influenced by the diet and vice versa, as the gut microbiota’s metabolism of different diet-derived compounds can influence the host’s health [ 45 ]. In particular, in addition to TMAO, several other gut microbiota-derived metabolites have been implicated in the enhancement of cardiovascular disease mortality, such as secondary bile acids and tryptophan and indole derivatives, as comprehensively described by Sanchez-Gimenez and collaborators [ 46 ].…”
Section: Trimethylamine N-oxide (Tmao)mentioning
confidence: 99%
“…Moreover, patients with heart failure have higher plasma Kyn level, and Kyn level may be used as an indicator to predict the incidence of myocardial infarction in patients with stable angina. 83 Sanchez-Gimenez et al 84 have conducted a prospective cohort study, they found positive associations between indole derivatives and major adverse CVDs, while a negative relationship was reported between tryptophan and all-cause mortality. They speculated the influence of tryptophan on mortality might depend on the degradation rate of kynurenine.…”
Section: Bile Acidmentioning
confidence: 99%
“…Sanchez-Gimenez et al 84 have conducted a prospective cohort study, they found positive associations between indole derivatives and major adverse CVDs, while a negative relationship was reported between tryptophan and all-cause mortality. They speculated the influence of tryptophan on mortality might depend on the degradation rate of kynurenine.…”
Section: Treatmentsmentioning
confidence: 99%